Regional restructuring, reindustrialization and development of the higher education - Horváth, Gyula (Acta Agraria Debreceniensis, 2012)
The development of the new economy in Hungary involves a complexity of economic and social processes. The sectoral structures and territorial location of the industy and the higher education show significant inequalities. Capital city concentration, low level of research orientation and insufficient linkages with industries are the most important barriers of the development of higher education and reindustrialization. The regional and cohesion policies need strong relations between economic restructuring and higher education development. The paper focuses on demonstrating the regional differences in these fields in southern and eastern Hungarian regions.